Is There an Effect of Economic Growth and Poverty Level in North Sulawesi? Data Analysis for 2003-2021 - irwandi; Andi Samsir; Muhammad Syafri; Munirah Diva Mawadani (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
This study aims to determine the effect of economic growth on the poverty rate in North Sulawesi Province in 2003-2021. The dependent variable in this study is poverty and the independent variable is economic growth. The data used is secondary data from related agencies, especially the Central Bureau of Statistics of North Sulawesi. Linear regression analysis became a data analysis technique in this study. The results of this study found that there was no significant effect of economic growth on poverty levels in North Sulawesi Province and the relationship was positive